Phytomedicinal armamentarium: A review of inula racemosa-derived alantolactones and isoalantolactones in anticancer therapy - Joshi Gaurav Santoshrao; Smriti Jamwal; Rakesh Kumar; Ekta Bisht; Bisen Harsh Krishnakumar; Shreya Katoch; R.K. Asrani (Phytomedicine Plus)
Background: Cancer remains a significant health challenge, with increasing incidence and mortality rates attributed to lifestyle factors and environmental pollutants. Despite decades of research, a universal cure for cancer remains elusive. The natural flora, particularly medicinal plants, offers a rich source of bioactive compounds with potential therapeutic benefits. Inula racemosa, a plant used in Ayurveda and Traditional Chinese Medicine, has been recognised for its various medicinal properties. Purpose: This review aims to summarize the recent research and advances concerning the anti-cancer effects of two key phytoconstituents—alantolactone and isoalantolactone—derived from Inula racemosa. The review focuses on understanding their mechanisms of action and potential as alternative cancer therapies. Methods: A comprehensive literature search was conducted using databases such as PubMed, Google Scholar, and Web of Science. Keywords like ''Inula,'' ''anticancer,'' and ''cell lines'' were employed to identify relevant studies. Initially 126 papers were screened in total and the collected data were analysed to assess the anti-cancer properties of alantolactone and isoalantolactone. Results: Studies indicate that alantolactone and isoalantolactone exhibit significant anti-cancer activities through various mechanisms. These include the induction of apoptosis, regulation of the cell cycle, inhibition of angiogenesis, and suppression of metastasis. The compounds have demonstrated efficacy in vitro and in vivo, affecting various cancer cell lines with minimal toxicity to normal cells. Conclusion: Alantolactone and isoalantolactone from Inula racemosa show promising potential as anti-cancer agents. Their diverse mechanisms of action and minimal side effects position them as candidates for further research and development. Future studies should focus on clinical trials to establish their efficacy and safety in humans, paving the way for new cancer therapies.